Anatomy of the Wage Gap Between Local and Migrant Workers in Urban Areas of the People’s Republic of China - SHU CAI; XINGJIAN ZHANG (Asian Development Review, 2025)
This paper examines the wage differentials between local and migrant workers in urban areas of the People’s Republic of China. Using unique data from a survey that was designed to be representative of migrants and local residents, the study finds that, without considering differences in the distribution of job attainment, the majority of the wage gap can be explained by differences in personal characteristics. However, an examination of labor market segmentation indicates that a significant component of the cross-group wage differentials due to segmentation in jobs with different work times or tenures is unexplained by productivity-related characteristics, implying possible discrimination against migrant workers along these aspects.